2010
DOI: 10.1143/apex.4.011101
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conducting and Very Thin ZnO:Al Films with ZnO Buffer Layer Fabricated by Solid Phase Crystallization from Amorphous Phase

Abstract: We propose a novel method of oxide crystal growth via atomic-additive mediated amorphization. By utilizing this method, solid-phase crystallization (SPC) of ZnO from amorphous phase has been successfully demonstrated via nitrogen atom mediation. The resultant SPC-ZnO films are highly orientated and the crystallinity is higher than that of the films prepared by conventional sputtering. By using the SPC-ZnO as a buffer layer, the resistivity of ZnO:Al (AZO) films is drastically decreased. 20 nm-thick AZO films w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…[11][12][13][14][15][16][17] However, it must be remembered that ρ and n (but not μ) require knowledge of the electrical thickness d el , which may not be the same as d. That is, the Hall effect does not directly measure a volume concentration n ðcm −3 Þ, but a sheet concentration n s ðcm −2 Þ. If n is uniform, then these two quantities are simply related by n ¼ n s ∕d el , where d el ¼ d − δd is the electrical thickness, the region that contains free electrons.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15][16][17] However, it must be remembered that ρ and n (but not μ) require knowledge of the electrical thickness d el , which may not be the same as d. That is, the Hall effect does not directly measure a volume concentration n ðcm −3 Þ, but a sheet concentration n s ðcm −2 Þ. If n is uniform, then these two quantities are simply related by n ¼ n s ∕d el , where d el ¼ d − δd is the electrical thickness, the region that contains free electrons.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…[5][6][7][8][9][10] The attractiveness of ZnO in these applications is partially due to the demonstrations of high-quality growth on many different substrates using many different growth techniques. However, a troubling problem is that films on lattice-mismatched substrates nearly always exhibit a thickness dependence of the electrical parameters, resistivity ρ, mobility μ, and carrier concentration n. [11][12][13][14][15][16][17] The origin of this problem seems to be connected with poor crystallinity near the substrate/layer interface. Recently, however, Itagaki et al 16,18,19 have demonstrated significant improvement in the crystallinity of radio frequency (RF)-sputtered ZnO by inserting a thin ZnON buffer layer between the substrate and ZnO layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The ultimate level of performance is achieved if columnar texture domains grow just from the interface. 2 Another approach is covering a glass substrate with a ZnO buffer layer [5][6][7] so that it acts a virtual template for pseudoepitaxial growth. The subsequently deposited conductive film has superior crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have developed a novel fabrication method of sputtered ZnO films utilizing nitrogen-atom mediated crystallization (NMC) [7,8]. The ZnO films have well aligned crystal orientation and higher crystallinity than the films prepared by a conventional sputtering because the nucleation density can be reduced by using the NMC method.…”
Section: Introductionmentioning
confidence: 99%